1982
DOI: 10.1128/jcm.16.5.948-952.1982
|View full text |Cite
|
Sign up to set email alerts
|

Practical procedure for demonstrating bacterial flagella

Abstract: We developed a simple, rapid method for demonstrating bacterial flagella with Ryu staining solution that gave satisfactory results for numerous motile and nonmotile bacteria. Two major advantages of this method are that the staining solution, ready for use, is stable at ambient temperature indefinitely and that microscopic examination of bacteria in the stained drop preparations can be performed rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
4

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(51 citation statements)
references
References 7 publications
0
47
0
4
Order By: Relevance
“…Spore stain was performed by Schaeffer and Fulton's method (3). Flagella stain was performed by the method described by Kodaka et al (8). Motility was examined by the hanging drop method (12).…”
Section: Methodsmentioning
confidence: 99%
“…Spore stain was performed by Schaeffer and Fulton's method (3). Flagella stain was performed by the method described by Kodaka et al (8). Motility was examined by the hanging drop method (12).…”
Section: Methodsmentioning
confidence: 99%
“…All strains were initially screened by Gram stain, cytochrome oxidase test (Gerhardt et al 1981), and identified with the API 20NE Test System for non-fermenters or the API 20E for fermentative bacteria (API System, S.A., La Balme les Grottes, France) according to manufacturers' instructions. Additional tests included flagella staining (Kodaka et al 1982), pigment production on Pseudo P and Pseudo F media (Difco) after incubation at 22°C for 10 d, growth in nutrient broth at 41.5"C for 24 h, lecithinase production, and growth in 6.5% NaCl (Gilardi 197 (ATCC 7965).…”
Section: E N U M E R a T I O N Isolation A N D I D E N T I F I C A mentioning
confidence: 99%
“…We found both LF82 and LF82 Δ LF82_314 are more enriched in capillaries containing glucose than without, and no statistically significant difference was observed, suggesting chemotaxis is intact in LF82 Δ LF82_314 . We also assessed whether the number per cell or morphology of flagella was affected by deletion of LF82_314 , using Kodaka staining [65] and transmission electron microscopy (TEM). Kodaka staining (Fig.…”
Section: Resultsmentioning
confidence: 99%